2010
DOI: 10.3390/molecules15052949
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Suzuki-Miyaura Reaction: Application to the Microwave-promoted Synthesis of 4,7-Diarylquinazolines

Abstract: New diarylquinazolines displaying pharmaceutical potential were synthesized in high yields from 4,7-dichloro-2-(2-methylprop-1-enyl)-6-nitroquinazoline by using microwave-promoted regioselective Suzuki-Miyaura cross-coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In many instances, microwave heating has been shown to dramatically reduce processing times, increase product yields and to enhance product purities or material properties compared to conventionally processed experiments. [12][13][14][15][16][17] Although a variety of different microwave reactors and processing options are available today, 18 the overwhelming majority of all currently published microwave synthesis protocols describe the use of this non-classical heating principle in conjunction with sealed reactors. 12,13 Thus, substrate 1 was reacted with an excess of 2aminobenzothiazole in various reaction conditions, 3 including microwave-assisted and solvent-free ones, 6 in both sealed reactors and open flasks.…”
Section: Resultsmentioning
confidence: 99%
“…In many instances, microwave heating has been shown to dramatically reduce processing times, increase product yields and to enhance product purities or material properties compared to conventionally processed experiments. [12][13][14][15][16][17] Although a variety of different microwave reactors and processing options are available today, 18 the overwhelming majority of all currently published microwave synthesis protocols describe the use of this non-classical heating principle in conjunction with sealed reactors. 12,13 Thus, substrate 1 was reacted with an excess of 2aminobenzothiazole in various reaction conditions, 3 including microwave-assisted and solvent-free ones, 6 in both sealed reactors and open flasks.…”
Section: Resultsmentioning
confidence: 99%
“…We report herein the synthesis of such molecules from the reaction in water of 4-chloromethyl-2-methyl-5-nitro-1,3-thiazole ( 1 ) with various sulfinate anions under microwave irradiation. This is in continuation of our research program directed towards the study of electron transfer reactions in heterocyclic series [ 25 , 26 ] and microwave-assisted [ 27 , 28 ] eco-friendly processes [ 29 , 30 ]. The antiproliferative activity both of sulfones and of some α-dichlorinated sulfonyl derivatives was comparatively evaluated on the CHO and HepG2 cell lines, and results confirmed the promising antiproliferative effect of dihydrogenated sulfones towards the HepG2 cell line.…”
Section: Introductionmentioning
confidence: 82%
“…The first highly selective C‐4 Suzuki–Miyaura arylation of a 4,7‐dichloroquinazoline derivative was recently reported by Kabri et al 181. They investigated the reaction conditions providing site‐selectivity between the 4‐ and 7‐chlorinated positions of 4,7‐ dichloro‐2‐(2‐methyl‐1‐propenyl)‐6‐nitroquinazoline ( 489 ) and found that under the optimized conditions illustrated in Scheme the microwave‐promoted Pd(PPh 3 ) 4 ‐catalyzed reaction of this substrate with arylboronic acids led to the monosubstituted products 490 in 48–72% yields with complete site‐selectivity.…”
Section: Cross‐coupling Reactions Of Polyhalogenated Six‐membered Hmentioning
confidence: 99%
“…of arylboronic acids Ar 2 B(OH) 2 in a 9:1 mixture of DMF and EtOH at 150 °C for 3 h in the presence of 3.0 equiv. of Na 2 CO 3 181…”
Section: Cross‐coupling Reactions Of Polyhalogenated Six‐membered Hmentioning
confidence: 99%